Insights, challenges, and strategies of teachers in the integration of traditional Filipino games in music, arts, physical education, and health instruction - Belano, Rojane Faith; Perez, Rexomar D. (Technium Social Sciences Journal, 2024)
Traditional Filipino games are activities played across generations, making use of local resources. This study aimed to gain a better understanding of teachers’ experiences with integrating traditional Filipino games into the Music, Arts, Physical Education, and Health (MAPEH) instruction of local public schools. Utilizing a basic qualitative research design, this study sought to grasp the present scenario in elementary schools through in-depth interviews and prolonged engagement with the six teachers chosen using inclusion criteria. Employing thematic analysis using Lichtman’s (2017) three Cs, three major themes with a total of thirteen subthemes emerged as key findings of this research: (1) Valuing Games for Education with Sub-themes, (a) Reminiscing Childhood Games, (b) Recognizing Games Positive Impact in the Classroom, (c) Treasuring Traditional Filipino Games, (2) Overcoming Obstacles with Sub-themes (a) Motivating Unengaged Learners to Move amidst Media and Technology, (b) Managing Unruly Learners during Games, (c) Lacking Facilities and Supplies, (d) Limiting Opportunities for Playtime, (3) Strategizing in a Dynamic Learning Environment with Sub-themes (a) Encouraging Active Exploration, (b) Using Cues and Procedures to Refocus Positive Behavior (c) Improvising Space and Materials (d) Initiating Opportunities for Play, (e) Using Differentiated Playing Experiences, (f) Collaborating with Other Teachers. The results of this research provide supporting baseline data for enhancing the delivery of MAPEH instruction and promoting relevant, indigenized, and localized education through traditional games.